Effect of Servant Leadership and Political Will Perception Toward Managerial Performance - RIFA'I, AHMAD; Tan, Syamsurijal; Edward, Edward; Adriani, Zulfina (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Purpose – This trying to test whether political will perception is able to mediate the influence of servant leadership on managerial performance Methodology/approach –This research uses quantitative methods. Data processing and hypothesis testing using WarPLS version 7.0. This research was conducted at the Government of Indragiri Hilir Regency, Riau Province, Indonesia. The sampling technique used is probability sampling with proportionate stratified random sampling. The sample was calculated using Herry King's Nomogram Table with an error rate of 5% where 135 respondents were selected. Findings – ItFound that. Political will perception is able to mediate the influence of servant leadership on managerial performance. The direct influence of Servant leadership on managerial performance is greater than the direct influence of political will perception on managerial performance. There is a direct influence of servant leadership on political will perception. Novelty/value –Because political will perception has become an important factor that is able to mediate the influence of servant leadership on managerial performance, it is very important to understand how to maintain managerial performance by looking at indicators of political will perception.